Real‑Life Contexts of Spontaneous Family Life Education - Gabriella Pusztai; Katalin Pallay; Cintia Csók (Jesuit University Ignatianum in Krakow, 2024)
RESEARCH OBJECTIVE: The aim of the research is to explore how spontaneous family life education and preparation for adult life takes place in students' immediate environment in Hungary. THE RESEARCH PROBLEM AND METHODS: Our main research question is "what are teachers' and support professionals' perceptions of patterns of family life education in different family milieus?" The target group for the individual and focus group interviews was teachers working with grades 5-13 and school support staff (N = 53). THE PROCESS OF ARGUMENTATION: The theoretical basis of enhancing family life has undergone considerable change in recent decades. Several international studies have addressed the extreme context sensitivity of family and adult life education in societies with significant regional and social inequalities, such as Hungary, and have called for the compilation of a problem map on which adult life education is based. RESEARCH RESULTS: One important finding of the study is that spontaneous family life education in Hungarian families varies widely according to social and regional aspects. Four family models emerged from the analysis (rural low status, rural or small‑town strivers, urban middle class, and urban educated high status). CONCLUSIONS, RECOMMENDATIONS AND APPLICABLE VALUE OF RESEARCH: Preparation for various aspects of adult life is a challenging school task that requires special preparatioand extra work by teachers and school support staff. Because of the dialogue between spontaneous family life education and family life education in schools, there is no uniform curriculum and method for family life education that can be used in all social contexts.